Best Answer

a + b - 2 is the answer in simplest terms. without telling us what a or b is this is the most accurate answer.

Q: What is 3a plus 2b-6-2a-b plus 4?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

It is 6a + 4

4a+3a-4 = 10 4a+3a = 10+4 7a = 14 a = 2

7a minus 2, if "3a-2" means 3a minus 2. 3a plus 1 and 1-3rd in parenthesis times 3a, if "3a-2" means 3a squared. a plus 3a squared plus 3a = 1-3rd times 3a plus 3a times 3a plus 1 times 3a = 3a plus 1 and 1-3rd in parenthesis times 3a

3(a+4) = 3a+12

(5a+8) - (2a+4) =3a +4 To do this, simply subtract like terms. 5a-2a=3a and 8-4=4

Related questions

It is 6a + 4

2a + 3a + 4 = 5a + 4

3a plus 4 equals 3a +4. You can not combine the two parts because they are not like terms so there is no way to simplify this.

(3a - 4)(3a - 4)

It can be simplified to: 3a^2 +10a+7 or factored as (3a+7)(a+1)

4a + 3a = (4 + 3)a = 7a

7a

4a+3a-4 = 10 4a+3a = 10+4 7a = 14 a = 2

7a minus 2, if "3a-2" means 3a minus 2. 3a plus 1 and 1-3rd in parenthesis times 3a, if "3a-2" means 3a squared. a plus 3a squared plus 3a = 1-3rd times 3a plus 3a times 3a plus 1 times 3a = 3a plus 1 and 1-3rd in parenthesis times 3a

a = 3a + 4 0 = 2a + 4 2a = -4 a = -2

3(a+4) = 3a+12

3a + a = 4a Example: a = 5 (3x5) + 5 = 15 + 5 = 20 = 4 x 5